Compressive properties of self-healing microcapsule-based cementitious composites subjected to freeze-thaw cycles using acoustic emission - Hao, Wenfeng; Hao, Hao; Kanwal, Humaira; Jiang, Shiping (Frontiers in Chemistry, 2022)
Microcapsule self-healing technology is an effective scheme to improve the durability of cementitious composites. In this paper, the compressive properties of microcapsule-based self-healing cementitious composites after freeze-thaw cycles were studied using acoustic emission (AE), and the changes in AE characteristics, compressive strength, mass loss rate, and electric flux of microcapsule-based self-healing cementitious composites with different microcapsule contents and freeze-thaw cycles were studied. The results show that if the content of the microcapsule is appropriate, with the increase in the number of freeze-thaw cycles, the AE hits will generally increase first and then decrease, and the early AE events will also decrease. Because of the different contents of microcapsules, the improvement effect and defect effect change dynamically with the number of freeze-thaw cycles, which is also reflected in the dynamic process of compressive strength. After 100 freeze-thaw cycles, the compressive strength of self-healing cementitious composite samples with 5% content of microcapsules and 3% content of microcapsules is the highest. The changes in mass loss rate and electric flux are similar to the AE characteristic parameters, which further verifies the results of AE. The research results of this paper provide experimental data and experimental methods for the engineering application of microcapsule self-healing cement-based composites in cold areas.